2003
DOI: 10.1302/0301-620x.85b1.13212
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic imaging of fractures of the clavicle in newborn infants

Abstract: Fractures of the clavicle in the neonate are usually diagnosed by clinical examination and confirmed by plain radiography. Exposure of newborn infants to irradiation should be avoided if possible. Following the clinical examination of 2978 neonates, 15 had suspected fractures of the clavicle. All were confirmed by ultrasound. In combination with clinical examination, ultrasound is a satisfactory alternative to radiological assessment for the diagnosis of fractures of the clavicle in newborn children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…MSUS is not the first-line imaging modality when bone trauma is suspected. However, it is worthwhile for detecting occult fractures that are not shown on radiographs, [11][12][13][14][15][16][17][18] as it may avoid more costly MRI. 6,11 MSUS can detect rib fractures in 6 times as many patients as radiography and will detect 10 times more fractures overall.…”
Section: Traumatic Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSUS is not the first-line imaging modality when bone trauma is suspected. However, it is worthwhile for detecting occult fractures that are not shown on radiographs, [11][12][13][14][15][16][17][18] as it may avoid more costly MRI. 6,11 MSUS can detect rib fractures in 6 times as many patients as radiography and will detect 10 times more fractures overall.…”
Section: Traumatic Lesionsmentioning
confidence: 99%
“…When pain, with or without swelling, is present in newborns and children after suspected bone trauma around a joint, findings on physical examination are usually nonspecific and radiographs are commonly nondiagnostic because the nonossified epiphyses are not visualized. 6,17,18,[22][23][24] In this situation, MSUS may become a reliable substitute for the plain radiographs in selected cases, 17,22 not only by visualizing the unossified cartilaginous bone, but also by correlating the symptoms and physical signs with sonographic findings ( Figure 5). Tenderness or pain elicited from a suspected lesion as the transducer passes over it is known as positive ''sonographic palpation.''…”
Section: Traumatic Lesionsmentioning
confidence: 99%
“…A critical study that analyzed 337 knee surgeries for distal femur size, revealed a wide aspect ratio (medial-lateral (M/L) dimension divided by the anterior-posterior (A/P) dimension) variation between the male and female populations [4]. Results from the study indicated that prosthetic manufacturers were skilled at supplying implant sizes that fit the average patient within the population of those undergoing TKA.…”
Section: Introductionmentioning
confidence: 99%
“…A similar mismatch occurs for other manufactures. For example, Duracon (Stryker Howmedica Ostenics) exhibits an average overhang of 4.9 mm for women and only −0.1 mm for men [4]. Such medial or lateral overhang has been conjectured to result in soft tissue irritation complicated balancing efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have documented the utility of sonography in the diagnosis of fractures of the clavicle in neonates. 13,14 Kayser et al 13 showed sonography and the clinical examination to be acceptable alternatives to plain radiography in such evaluations, allowing avoidance of thyroid irradiation. Blab et al 14 found no significant difference in diagnostic accuracy for infantile clavicular fractures assessed by sonography and plain radiography.…”
mentioning
confidence: 99%